Risk factors for gastric cancer: an umbrella review of systematic reviews and meta-analyses - Liang, Jin Long; Yuan, Hui Ming; Quan, Chao; Chen, Jun Qiang (Frontiers in Oncology, 2025)
BackgroundThis umbrella review aims to critically appraise and synthesize epidemiological evidence from meta-analyses to identify and classify risk and protective factors associated with gastric cancer.MethodsPubMed, Embase, Web of Science, and the Cochrane were used to search, including meta-analyses up to April 2024. Emphasis was placed on non-interventional studies, and the inclusion criteria focused on meta-analyses that involved diverse ethnic groups and genders from various countries and settings. Two reviewers independently evaluated the methodological quality using the AMSTAR tool and classified evidence strength based on established criteria.ResultsOf 245 meta-analyses meeting inclusion criteria, 117 unique risk factors were identified, including 77 significantly associated factors (42 adverse and 35 protective) and 40 non-significant factors. 17 (14.5%) risk factors were classified as class I or II evidence in this umbrella review. Protective factors included cruciferous vegetable intake, total cholesterol (TC), HDL cholesterol (HDL-C), NSAIDs, β-carotene, vitamins, and dietary polyphenols. Risk factors included depression, Helicobacter pylori (Hp) infection, dermatomyositis, and Graves’ disease. Class III evidence confirmed that aspirin, non-aspirin NSAIDs, soy food intake, non-fermented soy food intake, physical activity, vitamin A, ginseng, dietary fiber, tooth brushing frequency, folate, and green tea consumption were associated with reduced GC risk. Conversely, Epstein-Barr virus infection, red meat, processed meat, intestinal metaplasia, gastric atrophy, a western-style diet, dietary cholesterol, dietary salt, and proton pump inhibitors were linked to higher GC risk.ConclusionThis umbrella review identified 77 risk factors significantly associated with gastric cancer (GC), the majority of which are linked to personal traits and lifestyle behaviors. These findings enhance our understanding of GC etiology and can inform strategies to reduce incidence, delay progression, and alleviate the global burden.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023447199.